Про ідентифікаційну модель динаміки дискретного спостережуваного неоднорідно-розподіленого просторово-часового процесу - Скопецький, В.В.; Стоян, В.А. (Видавничий дім "Академперіодика" НАН України, 2007)
A pseudoinverse approach to constructing the integral models of spatio-temporal distributed systems by a discretely observed state and an externally distributed dynamic disturbance has been offered. The problem of control over these systems has been solved. The results obtained are illustrated.